Addressing NCDs: A unifying agenda for sustainable development. Issue 9 (2nd September 2018) - Collins, Téa; Mikkelsen, Bente; Adams, Jennifer; Chestnov, Oleg; Evans, Tim; Feigl, Andrea; Nugent, Rachel; Pablos-Mendez, Ariel; Srivanichakorn, Supattra; Webb, Douglas
ABSTRACT: Despite the mounting evidence that they impede social and economic development, increase inequalities, and perpetuate poverty, Noncommunicable diseases (NCDs) remain largely absent from the agendas of major development assistance initiatives. In addition, fundamental changes are developing in patterns of development assistance for health, and more of the burden for fighting NCDs is being placed on domestic budgets, thus increasing pressure on the most vulnerable countries. The paper argues, however, that a new day is coming. With the inclusion of NCDs and related targets in the 2030 Agenda for Sustainable Development, there is an unprecedented opportunity to explore linkages among the sustainable development goals, enhance policy coherence and advance the NCD agenda as part of sustainable development. International development partners (bilateral and multilateral) can help in this important effort to address NCDs and their shared risk factors by providing catalytic support to countries that are particularly vulnerable in terms of the disease burden but lack the resources (human, financial) and institutional arrangements to meet their commitments at national, regional, and global levels.